The Influence of Perceptions of Organizational Support, Organizational Justice and Leadership Style on Job Satisfaction: The Mediating Role Organizational Commitment (Case Study of PT. XYZ Employees) - Nurhasanah Nurhasanah; Nurul Hermina (Dinasti Publisher, 2025)
This study aims to analyze the effect of perceived organizational support, organizational justice, and leadership style on employee job satisfaction with organizational commitment as a mediating variable (case study of PT. XYZ). The method used in this study is a quantitative method with a descriptive verification approach. Data were collected using a questionnaire distributed to 103 employees of PT. XYZ. The sample size was determined using a non-probability sampling technique, which is a sampling technique that does not provide an opportunity or chance for each member of the population to be selected as a sample. This study selected samples from the entire population of 103 people. The tool used to analyze the data in this study was SmartPLS-23, 2024. The data obtained were analyzed using the Structural Equation Modeling (SEM) technique to test the relationship between variables. The results showed that perceived organizational support did not have a positive effect on organizational commitment, but there was a direct effect on job satisfaction while organizational justice and leadership style had a positive effect on organizational commitment, which then affected job satisfaction and confirmed the mediating role of organizational commitment between organizational justice on job satisfaction and leadership style on job satisfaction. The statistical results show significant t-statistics and p-values, indicating a strong predictive relevance of the model. The statistical results of leadership style on job satisfaction directly show weak t-statistics and p-values, so that leadership style does not have a direct effect on job satisfaction, but has a positive effect through organizational commitment, which then affects job satisfaction. This indicates the need for increased support and fairness from the organization to increase employee commitment and job satisfaction. In particular, the results of the study highlight the need for a better leadership style strategy to achieve more optimal employee loyalty and job satisfaction.